2022
DOI: 10.1152/japplphysiol.00178.2022
|View full text |Cite
|
Sign up to set email alerts
|

Blood flow restriction and stimulated muscle contractions do not improve metabolic or vascular outcomes following glucose ingestion in young, active individuals

Abstract: Glucose ingestion and absorption into the blood stream can challenge glycemic regulation and vascular endothelial function. Muscular contractions in exercise promote a return to homeostasis by increasing glucose uptake and blood flow. Similarly, muscle hypoxia supports glycemic regulation by increasing glucose oxidation. Blood flow restriction (BFR) induces muscle hypoxia during occlusion and reactive hyperemia upon release. Thus, in the absence of exercise, electric muscle stimulation (EMS) and BFR may offer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 74 publications
1
5
0
Order By: Relevance
“…Overall, changes in muscular strength in all three groups tended to improve. This is consistent with previous studies that blood flow restriction training was found to improve muscular strength (Cai et al, 2021;Cohen et al, 2022) or even whole-body vibration training alone can also increase muscular strength (Berner et al, 2020;Hegazy et al, 2021;Lai et al, 2021). This was especially true in the WBV+HYP group, where changes were similar to those in the BFR group.…”
Section: Discussionsupporting
confidence: 92%
“…Overall, changes in muscular strength in all three groups tended to improve. This is consistent with previous studies that blood flow restriction training was found to improve muscular strength (Cai et al, 2021;Cohen et al, 2022) or even whole-body vibration training alone can also increase muscular strength (Berner et al, 2020;Hegazy et al, 2021;Lai et al, 2021). This was especially true in the WBV+HYP group, where changes were similar to those in the BFR group.…”
Section: Discussionsupporting
confidence: 92%
“…To our knowledge seven studies have reported the acute effects of NMES on substrate utilization measured by Respiratory Quotient (RQ) or Respiratory Exchange Ratio (RER), oxygen consumption (VO2), and lactate production. All these studies indicate increased glucose utilization during NMES application as measured by increased RQ ( 50 , 51 , 77 , 78 , 83 , 84 ), increased lactate level ( 50 , 51 , 61 , 77 , 78 ) or elevated oxygen utilization ( 50 , 51 , 77 , 78 , 83 ) (see Table, Supplementary Table 2 ). Additionally, three studies reported on energy expenditure during NMES.…”
Section: Resultsmentioning
confidence: 99%
“…Two other studies reported an increase in whole body carbohydrate utilization using a Douglas Bag method ( 84 ) while Cohen et al. showed an additive effect of NMES with blood flow restriction on carbohydrate utilization ( 83 ). An increased whole body oxygen uptake measured by RER has been noted at the onset of low frequency electrical stimulation, followed by an immediate return to resting levels at the termination of stimulation ( 77 , 78 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations